MODELLING AND MEASUREMENT OF NOx CONCENTRATION IN PLUME FROM AIRCRAFT ENGINE UNDER OPERATION CONDITIONS AT THE AERODROME AREA - Zaporozhets, Oleksandr; Synylo, Kateryna (Proceedings of National Aviation University (archive), 2016)
Purpose: Airport air pollution is growing concern because of the air traffic expansion over the years (at annual rate of 5 %), rising tension of airports and growing cities expansion close each other (for such Ukrainian airports, as Zhulyany, Boryspol, Lviv, Odesa and Zaporizhzhia) and accordingly growing public concern with air quality around the airport. Analysis of inventory emission results at major European and Ukrainian airports highlighted, that an aircraft is the dominant source of air pollution in most cases under consideration. For accurate assessment of aircraft emission contribution to total airport pollution and development of successful mitigation strategies, it is necessary to combine the modeling and measurement methods. Methods: Measurement of NOx concentration in the jet/plume from aircraft engine was implemented by chemiluminescence method under real operating conditions (taxi, landing, accelerating on the runway and take-off) at International Boryspol airport (IBA). Modeling of NOx concentration was done by complex model PolEmiCa, which takes into account the transport and dilution of air contaminates by exhaust gases jet and the wing trailing vortexes.Results: The results of the measured NOx concentration in plume from aircraft engine for take-off conditions at IBA were used for improvement and validation of the complex model PolEmiCa. The comparison of measured and modeled instantaneous concentration of NOx was sufficiently improved by taking into account the impact of wing trailing vortices on the parameters of the jet (buoyancy height, horizontal and vertical deviation) and on concentration distribution in plume. Discussion: Combined approach of modeling and measurement methods provides more accurate representation of aircraft emission contribution to total air pollution in airport area. Modeling side provides scientific grounding for organization of instrumental monitoring of aircraft engine emissions, particularly, scheme for disposition the monitoring stations with aim to detect maximum concentration which is characterized for jets/plumes from aircraft engines.